Determination of Trace Amounts of Aniline in Mixed Water-Ethanol Solution by Coulometric Titration - ATTARAN, A.M.; PARHAM, H.; RAEISZADEH, M. (Asian Journal of Chemistry, 2010)
A sensitive and simple constant current coulometric method is introduced for determination of aniline in the presence of sulfite (major interfering substance) in mixed water:ethanol (80:20) solution. Formaldehyde or acetaldehyde can mask the sulfite component. Measurement of coulometric time of the analyte in the solution mixture in which sulfite is masked by formaldehyde can be used to determine the concentrations of aniline. Relative standard deviations (RSD ) of all measurements lie in the range of 0.1- 2.1 %. The effect of different parameters such as pH, concentration of reagents, salt concentration and effect of interferences are studied. The proposed method can determine 1.0 × 10-7 moles of aniline in the presence of large amounts of sulfite masked by formaldehyde. The current efficiency of the method is estimated to be ≥ 98.5 %. The proposed method can be used for the determination of aniline in the presence of real sample matrixes (such as tap water) with good accuracy and precision.